2021
DOI: 10.7717/peerj-cs.624
|View full text |Cite
|
Sign up to set email alerts
|

Using of n-grams from morphological tags for fake news classification

Abstract: Research of the techniques for effective fake news detection has become very needed and attractive. These techniques have a background in many research disciplines, including morphological analysis. Several researchers stated that simple content-related n-grams and POS tagging had been proven insufficient for fake news classification. However, they did not realise any empirical research results, which could confirm these statements experimentally in the last decade. Considering this contradiction, the main aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…The sophisticated architecture with syntactic features proposed by Gupta et al [2021] presented an increase of up to 3 % in the performance. Kapusta et al [2021] noticed an accuracy increase by 3 to 4 %, where the average accuracies for syntactic, readability, and combined features are 84.12%, 77.67%, and 84.52%, respectively. Nguyen et al [2019] identified that n-grams in combination with dependency sub-trees as features have a positive impact on the performance of the classifier.…”
Section: What Are the Effects Of Incorporating Syntactic Information ...mentioning
confidence: 94%
See 1 more Smart Citation
“…The sophisticated architecture with syntactic features proposed by Gupta et al [2021] presented an increase of up to 3 % in the performance. Kapusta et al [2021] noticed an accuracy increase by 3 to 4 %, where the average accuracies for syntactic, readability, and combined features are 84.12%, 77.67%, and 84.52%, respectively. Nguyen et al [2019] identified that n-grams in combination with dependency sub-trees as features have a positive impact on the performance of the classifier.…”
Section: What Are the Effects Of Incorporating Syntactic Information ...mentioning
confidence: 94%
“…Zhou et al [2020] saw no improvement with shallow syntax, but deep syntax-level features (CFGs) and features at lexicon-level (BOWs) outperform the others. Kapusta et al [2021] concluded that morphological analysis can be applied to fake news classification.…”
Section: What Are the Effects Of Incorporating Syntactic Information ...mentioning
confidence: 99%
“…The occurrence frequency of all grams is counted and filtered according to the preset threshold to form a list of key grams. N-gram language model shows good performance in many text mining tasks (30)(31)(32). For example, Giannakopoulos and Karkaletsis (30) expressed the text as an n-gram model using a sliding window with a length of n by connecting the adjacent n-grams with the edges representing their co-occurrence frequency in a given text window, they captured the word order in the text and detected some similarities in the text morphology.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…This accuracy was lower than that obtained using word n ‐grams (96.8%) and higher than that obtained using character n ‐grams (87.1%). Zafarani et al (2019) and Kapusta et al (2021) used parts of POS tag n ‐grams as morphological characteristics of words to detect fake news. POS tag n ‐grams can also be used to predict author personality (Litvinova et al, 2015).…”
Section: Basic Feature Metricsmentioning
confidence: 99%